Genetic variability and breeding potential of barley (Hordeum vulgare L) landraces from north Shewa in Ethiopia - Gebeyaneh, Alemayehu Assefa (University of the Free State, 2003)
Genetic variability and breeding potential of barley landraces from north Shewa in Ethiopia was studied with the aims i) to generate information about the level of diversity within and among the landraces in terms of morphological descriptors, SDSPAGE of seed storage proteins, and Amplified Fragment Length Polymorphism (AFLP) ii) to assess yield relationships and expected genetic advance that may be achieved through selection within or among landraces iii) to estimate genetic variances for agronomic characters from crosses involving selected barley landrace lines and predict the breeding potential of landraces and iv) to prove genetic differences between landraces, claimed by farmers, in response to waterlogging stress. The phenotypic diversity of 44 landraces, including farmers' cultivars, was estimated using Shannon Weaver diversity index for different qualitative an~ quantitative characters. This was further supplemented with SDS-PAGE of seed storage proteins and the two measures of variability were compared. Of the 44 landraces, emphasis was given to farmers' cultivars from which five to six pure line derivations from them were evaluated under field conditions to assess potential differences for agronomic characters and to estimate genetic advance that may be achieved through selection within the cultivars. Variability between lines within the cultivars for the quantitative characters was further assessed with the help of SDS-PAGE. Diallel crossing between five selected landrace lines differing in agronomic characters was carried out and genetic parameters and breeding potential of the parents were estimated. Three of the parents used for crossing were further investigated for their differences in growth and nutrient accumulation under waterlogging stress in a greenhouse pot experiment. Both morphological and SDS-PAGE data demonstrated the variability existing in the landraces. H'values pooled over morphological characters ranged from 0.12±0.08 to 0.57±0.11. Among the qualitative characters, landraces showed higher levels of polymorphism for spike type than for kernel colour, spike density and caryopsis type (covered or naked). Caryopsis type was the least diverse character observed. Diversity for quantitative characters pooled over landraces was generally very high especially for number of seeds spike" and days to maturity with respective H' values of 0.90 and 0.98. SDS-PAGE data based on representative lines from each landrace showed very low to high within landrace variability. Lines from landraces differed from each other in number and migration distances of bands. Some landraces that looked uniform for spike morphology also showed differences in banding patterns. It was also observed that some landraces displaying different spike characters, and hence assumed to exhibit differences of comparable magnitude in storage protein variability, did not reveal much differences. Variability between landraces was higher than within landraces and variability within farmers' cultivars was lower than within accessions. Clustering results of landraces from SDS-PAGE data were different in composition from those formed by morphological characters. Clustering from morphological data highlighted distinct grouping of landraces based on similarities in morphological characters whereas SDSPAGE data did not depict such distinctness. AFLP analysis of the genetic relationships between farmers' cultivars using six primer combinations illustrated varying degrees of genetic dissimilarity (0.372 to 0.728) with a mean of 0.545. Thirty one percent of the values in this range were 0.500 while 69 % of the values were > 0.600 demonstrating the presence of sufficient variation between the farmers' cultivars. The number of scoreable fragments amplified by each AFLP primer combination varied from 49 to 118 with an average of 84.5 and polymorphic fragments for each primer combination varied from 27 to 77 the average being 58.5. The average percent polymorphism was 69.9 % with values ranging from 55.1 % to 75.8%. Field evaluation of pure lines from farmers' cultivars indicated that genetic gain through selection for yield and yield components within the farmers' cultivars from this particular environment is minimal. Selection may even end up with negative gain unless carefully carried out to isolate those that might be useful to bring slight improvement in yield. Carefully excluding the inferior types to upgrade yield potential is suggested rather than attempting to improve them through extensive pure line selection and evaluation methods. Evaluation of landraces from other sources, from within or outside this parrticular environment, is suggested to get better yielding landraces than the existing ones. In the long term, crossing may be scheduled between cultivars which, based on morphological characters and protein profiles, appear to be diverse in order to maximize the potential gain from selection in the progeny. Estimated genetic parameters from diallel crosses of barley landrace lines highlighted the importance of additive gene actions for spike length, number of seeds spike¹ and grain yield spike¹under free drainage conditions and for days to heading and days to maturity at both treatment levels. Both additive and non-additive gene actions were important in the control of grain yield under free drainage conditions. By contrast, estimates of genetic parameters for yield and yield components (except spike length) were very low or negative under waterlogged conditions. Among the parents, Feres Gama(37) and 1153(28) contributed the highest positive GCA effects and comparable SCA variances for yield and yield components under free drainage conditions. Hence, these parents shall be tested thoroughly in order that maximum use of their superior combining ability can be made in future crossing programs for environments free of waterlogging stress. A separate crossing and selection program is suggested for the respective environmental conditions if resources permit. Waterlogging reduced the total number of tillers per pot of the tolerant landrace Mage(07) and Feleme(68) by 43 % and 48 %, respectively compared to the control plants while it was only 23 % for the susceptible landrace Feres Gama(37). Total shoot dry matter accumulation under waterlogged conditions was comparable for all three landraces in spite of the largest number of tillers produced by Feres Gama(37). Differences between the susceptible and tolerant landraces in response to waterlogging were largely due to less dry matter accumulation of the tillers and slower growth in the susceptible landraces. Moreover, apparent differences were noticed in P concentration and uptake between the tolerant and susceptible landraces, the effect being less for the tolerant landrace Mage(07) than for the susceptible landrace Feres Gama(37). Difference in N concentration of shoots between Feres Gama(37) and Mage(07) was also observed although the magnitude was not comparable to that of P.

Genetiese variabilitieit en teel potensiaal van gars landrasse van noord Shewa in Etiopië is bestudeer met die doelom (i) inligting te genereer oor die vlak van diversiteit binne en tussen die landrasse in terme van morfologiese beskrywers, SDS PAGE van saad storings proteïene, en AFLP (Amplified Fragment Length Polymorphism) (ii) om opbrengs verwantskappe en verwagte genetiese vordering wat gekry kan word deur seleksie te bepaal tussen en binne landrasse (iii) om genetiese variansies te bepaal vir agronomiese eienskappe wat kruisings insluit van geselekteerde gars landras lyne en om die teel potensiaal van landrasse te bepaal (iv) om genetiese verskille tussen landrasse wat deur boere gerapporteer is te bevestig vir reaksie op versuipings stremming. Die fenotipiese diversiteit van 44 landrasse, insluitend boere cultivars, is bepaal met die Shannon Weaver diversiteits indeks vir verskillende kwantitatiewe en kwalitatiewe eienskappe. Dit is verder aangevul met SDS-PAGE van saad storings proteïene en die twee metings van variabiliteit is vergelyk. Van die 44 landrasse, is klem geplaas op die boere cultivars waarvan vyf tot ses ontwikkelde suiwer lyne geëvalueer is onder veld toestande om potensiële verskille in agronomiese eienskappe te bepaal en om genetiese vooruitgang te bepaal wat gemaak kan word deur seleksie binne hierdie cultivars. Variabiliteit tussen lyne binne cultivars vir die kwantitatiewe eienskappe is verder geëvalueer met die hulp van SDS-PAGE. 'n Dialleel kruising tussen vyf geselekteerde landras lyne met verskillende agronomiese eienskappe is gedoen, en genetiese parameters en telings potensiaal van die ouers is vasgestel. Drie van die ouers wat gebruik is in kruisings is verder ondersoek vir verskille in groei en voedingstof akkumuisie onder versuipings stremming in 'n glashuis pot proef. Beide morfologiese en SDS-PAGE data het getoon dat variabiliteit bestaan in die landrasse. H' waardes wat gepoel is oor morfologiese eienskappe het gewissel van 0.12±0.08 tot 0.58±O.ll. Binne kwalitatiewe eienskappe het landrasse hoër vlakke van polimorfisme getoon vir aar tipe as vir korrel kleur, aar kompaksie en kariopsis tipe (bedek of nakend). Kariopsis tipe was die minste diverse eienskap wat gesien is. Diversiteit vir kwantitatiewe eienskappe gepoel oor landrasse was oor die algemeen baie hoog, veral vir saad per aar en dae tot volwassenheid met H' waardes van 0.90 en 0.98. SDS-PAGE data, gebasseer op verteenwoordigende lyne van elke landras het baie lae tot hoë binne landras variabiliteit getoon. Lyne van landrasse het verskil van mekaar in aantal en migrasie afstande van bande. Sommige landrasse wat univorm gelyk het vir aar morfologie het verskille in bandpatrone getoon. Daar is ook gesien dat sekere landrasse wat verskillende aar eienskappe toon, en waar storings proteïen band verskille verwag is, het nie veel verskille getoon nie. Variabiliteit tussen landrasse was hoër as binne landrasse, en variabiliteit binne boere cultivars was laer as binne ander inskrywings. Groeperings resultate van SDS-PAGE data was verskillend in samestelling van die van morfologiese eienskappe. Groepering van morfologiese data het definitiewe groepe landrasse gegee gebasseer op ooreenkomste in morfologiese eienskappe, terwyl SDS-PAGE nie dieselfde gewys het nie. AFLP analise van genetiese verwantskappe tussen boere cultivars met ses priemstuk kombinasies het verskillende vlakke van genetiese verskille (0.372 tot 0.728) aangetoon met 'n gemiddeld van 0.545. Een en dertig persent van die waardes in hierdie reeks was ≤;0.500 terwyl 69% van waardes ~ 0.600 wat die teenwoordigheid van genoeg variasie bewys tussen boere cultivars. Die aantal bruikbare fragmente geamplifiseer deur elke AFLP priemstuk kombinasie het gevarieër van 49 tot 118 met 'n gemiddeld van 84.5 en polimorfiese fragmente van elke priemstuk kombinasie het gewissel van 27 tot 77, met 'n gemiddeld van 58.5. Die gemiddelde persentasie polimorfisme was 69.9% met waardes tussen 55.1 % tot 75.8%. Veld evaluasie van suiwer lyne van boere cultivars het getoon dat genetiese vooruitgang deur seleksie vir opbreangs en opbrengs komponente binne boere cultivars vir hierdie omgewing minimaal is. Seleksie kan selfs negatiewe vordering toon tensy dit versigtig gedoen word om daardie eienskappe te isoleer wat nuttig kan wees om 'n effense verbetering in opbrengs te gee. Versigtige uitsluiting van swak tipes om opbrengs potensiaal te verhoog is beter as intensiewe suiwer lyn seleksie en evaluasie metodes. Evaluasie van landrasse van ander bronne, van binne of buite die gebied is voorgestelom landrasse te kry wat beter opbrengs gee as die huidiges. In die lang termyn kan kruisings gemaak word tussen cultivars wat, gebasseer op morfologiese eienskappe en proteïen profiele, divers is sodat maksimum potensiaal vooruitgang gekry kan word van seleksie uit die nageslagte. Genetiese parameters vanaf dialleel kruisings van gars landrasse het die belangrikheid van additiewe geen aksie vir aar lengte, aantal sade per aar en graan opbrengs per aar onder vry dreinasie toestande en dae tot aarstoot en dae tot volwassenheid by beide behandelings, aangetoon. Beide additiewe en nie-additiewe geen aksies was belangrik in die beheer van graan opbrengs onder vrye dreinasie toestande. In teenstelling hiermee, was bepalings van genetiese parameters vir opbrengs en opbrengs komponente (behalwe vir aar lengte) baie laag of negatief onder versuipings toestande. Tussen die ouers, het Feres Gama(37) en 1153(28) die hoogste positiewe GCA effekte en vergelykbare SCA variansies vir opbrengs en opbrengs komponente onder vrye dreinasie gehad. Daarom sal hierdie ouers deeglik getoets word om maksimum gebruik van hulle goeie kombineervermoë te maak in toekomstige kruisings programme vir omgewings vry van versuipings stremming. 'n Aparte kruisings en seleksie program vir verskillende omgewings toestande word aanbeveel as hulpbronne dit toelaat. Versuiping het die aantal stamme per pot by die tolerante landrasse Mage(07) en Feleme(68) met 43% en 47% afsonderlik verminder in vergelyking met die kontrole plante maar vir die vatbaar landras Feres Gama(37) was dit net 23%. Totale stam droë materiaal akkumulasie onder versuipings toestande was vergelykbaar vir al drie die landrasse al het Feres Gama(37) die meeste stamme geproduseer. Verskille tussen vatbare en tolerante landrasse in reaksie op versuiping was grootliks a.g.v. minder droë materiaal in die stamme en stadiger groei in die vatbare landrasse. Verder was daar duidelike verskille in P konsentrasie en opname tussen tolerante en vatbare landrasse, waar die effek minder was vir tolerante landras Mage(07) as vatbare landras Feres Gama(37). Verskille in Nkonsentrasie van stamme tussen Feres Gama(37) en Mage(07) was ook duidelik, maar die verskille was kleiner as vir P.
Thesis (Ph.D. (Plant Science (Plant Breeding))--University of the Free State, 2003
Keywords: Barley -- Genetics; Crop yields -- Ethiopia; Barley -- Breeding